Antimicrobial Effect of Mucoadhesive Films Prepared with Biogenic Silica Nanoparticles - Naomi Tritean; Bogdan Trică; Augusta Raluca Gabor; Anisoara Cimpean; Florin Oancea; Diana Constantinescu-Aruxandei (Proceedings, 2020)
Mucoadhesive films can be used to extend the action of different bioactive compounds in the oral cavity. [...]